Asuhan Keperawatan Pada Ny. S Keluarga Tn. K Dengan Gangguan Sistem Kardiovaskuler: Hipertensi Di Desa Kutayu Dukuh Krajan 2 RT 05 RW 02 Kecamatan Tonjong Kabupaten Brebes - Trio Fadriana; Tati Karyawati; Siti Fatimah (Lembaga Pengembangan Kinerja Dosen, 2023)
Hypertension causes high rates of morbidity (sickness) and mortality (death). Hypertension is an increase in blood pressure in systolic and diastolic that comes and goes or persists. Hypertension is pressure higher than 140/90mmHg (Pangestika et al., 2022). Hypertension is also called the silent killer because this disease does not have specific symptoms, can attack anyone, and can cause degenerative diseases, even death (Yanita N.I.S, 2022).